My first science book - Wilkes, Angela (New York : Knopf, 1990)
An introduction to the world of science, featuring simple experiments.
Booklist.
Kirkus Review.
School Library Journal.
5.6
5.6
K-3.
Keywords: Science -- Experiments -- Juvenile literature; Experiments; Science -- Experiments; Science -- Experiments